Studies on Foliar Feeding of Plant Growth Regulators and Micronutrients on fruiting attributes of Ber (Ziziphus mauritiana Lamk) fruits cv. Gola - Brijesh Patel; Bhagwan Deen (The Bioscan, 2026)
The present study was conducted on 6-year-old Ber (Ziziphus mauritiana Lamk.) plants grown under sodic soil conditions at the Production Processing of Fruits and User Waste Land, Akma, under the Department of Fruit Science, College of Horticulture & forestry, of Acharya Narendra Deva University of Agriculture and Technology, Kumarganj, Ayodhya, (U.P.) during 2023- 24 and 2024-25. The objective of the investigation was to evaluate the impact of foliar application of plant growth regulators and micronutrients on fruiting character of Ber cv. Gola fruits. The experiment was laid out in a RBD (Randomized Block Design) and data were collected on key preharvest parameters including Fruit setting time, Fruit setting (%), Fruit drop (%) and Fruit retention (%). Among the treatments, T12 (GA3 20 ppm + NAA 30 ppm + ZnSO4 0.5% + Borax 0.5%) consistently resulted in the minimize Fruit setting time, increased the Fruit setting (%), least the Fruit drop (%) and higher the Fruit retention (%) during both the years and pooled mean as compared to control. Keywords Ber, Fruit setting time, Fruit setting, Fruit drop and Fruit retention